Pivotal factors influencing the performance of construction projects in Mogadishu city, Somalia - Ahmed Abtidon, Abdi Aziz (2014)
Being an underdeveloped country, construction projects in Somalia are affected by many problems which include among others financial issues, delays and safety problems. The aim of this study is to assess the local factors affecting the performance of construction projects thereby creating awareness to the project team to improve project performance in Mogadishu city. The objectives of this study is to review the performance of construction projects in relation to their cost and time; to identify the contractor, consultant and client related factors that contribute to the poor performance of construction projects; to analyse the effects the design/bid/build method of procurement has on the performance of construction projects and to formulate recommendations that will improve the performance of the projects in Mogadishu. The study focus on building projects carried out in the city of Mogadishu in Somalia. The data were collected through questionnaires and interviews. The questionnaire was done online using Google form and the respondents are the clients, consultants and the contractors. A total of 6 projects were analysed to determine their performance in relation to their cost and time. The data from the questionnaires were analyzed using SPSS to calculate the average index. From the study, the performance of construction projects in relation to their cost and time is not doing as well as expected by both the contractors and the clients. The contractor, consultant and client related factors that contribute to the poor performance of construction projects, are; the contractors’ desire to maximize profit, fraudulent practices and the client emphasize in choosing lowest bid. The effects design/bid/build method of procurement has on the performance of construction projects are on the coordination among the project participants, scheduling and the cost of the project. The recommendations that can improve the performance of construction projects are the Somali government should set and hand strict punishment to overcome fraudulence activities, the awarding of license to contractors and consultants should be checked thoroughly to make sure they are competent and have the necessary tools to do their work, the contractors should improve on their estimation techniques and consider all the external factors that could affect their projects.